Fabrication of Hydrophobic Graphene-Cellulose Composite Paper Using Rice Husk Ash Silica - Sariwahyuni; Herlina Rahim; Hanim Istatik Badi'ah; Andi Haslinah; Mega Fia Lestari (CV. Get Press Indonesia, 2025)
This study presents the fabrication and characterization of a sustainable graphene–cellulose composite paper reinforced with rice husk ash (RHA)–derived amorphous silica. Silica was extracted via alkaline leaching–acid precipitation, yielding a porous, high-purity amorphous phase well-suited for reinforcement. Composite papers were prepared by incorporating varying loadings of graphene nanoplatelets (0.5–2 wt%) and silica (5–15 wt%) into cellulose pulp, followed by ultrasonication, vacuum filtration, and hot pressing. Structural and morphological analyses (FTIR, XRD, SEM) confirmed effective dispersion and strong filler–matrix interactions. The incorporation of graphene and silica significantly enhanced surface hydrophobicity, raising the water contact angle from 62.5° for neat cellulose to 152.7°—indicative of a near-superhydrophobic state. Mechanical testing revealed an optimal formulation (1 wt% graphene + 10 wt% silica) that improved tensile strength by 42% and Young’s modulus by 36% compared to neat cellulose. Higher filler concentrations slightly reduced tensile strength due to filler agglomeration. This work demonstrates a valorization pathway for low-cost agricultural residues to produce eco-friendly composite materials with superior mechanical and surface properties, suitable for applications in packaging, filtration, or protective coatings.